A Pt/AlGaN/GaN heterostructure field-effect transistor (HFET) prepared by an electrophoretic deposition (EPD)-gate approach. (October 2016) - Hung, Ching-Wen; Chang, Ching-Hong; Chen, Wei-Cheng; Chen, Chun-Chia; Chen, Huey-Ing; Tsai, Yu-Ting; Tsai, Jung-Hui; Liu, Wen-Chau
Highlights: A high-performance HFET was achieved by electrophoretic deposition (EPD) and gate-sinking approaches. The use of low-temperature deposition (EPD) provides good gate-Schottky properties. By preparing the suspension solution, the EPD approach could easily provide size-scalable nanoparticles. Temperature-dependent current-voltage ( I - V ) characteristics of an EPD-based HFET were comprehensively studied. Abstract: Based on an electrophoretic deposition (EPD)-gate approach, a Pt/AlGaN/GaN heterostructure field-effect transistor (HFET) is fabricated and investigated at higher temperatures. The Pt/AlGaN interface with nearly oxide-free is verified by an Auger Electron Spectroscopy (AES) depth profile for the studied EPD-HFET. This result substantially enhances device performance at room temperature (300 K). Experimentally, the studied EPD-HFET exhibits a high turn-on voltage, a well suppression on gate leakage, a superior maximum drain saturation current, and an excellent extrinsic transconductance. Moreover, the microwave performance of an EPD-HFET is demonstrated at room temperature. Consequentially, this EPD-gate approach gives a promise for high-performance electronic applications.